The Formation of Dentistry as A Profession and Scientific Discipline - Normuradov Nodirjon Alisherovich (Scholars Digest Publishing, 2023)
The article is devoted to the emergence and development of dentistry as a profession and scientific discipline. In the work, special attention is paid to the stages of its development, as well as the features of its evolution in the East, in particular Central Asia.
Keywords: Dentistry, teeth, ancient East, Hippocrates, Ibn Sina, science, medicine, anesthesia, Muslim East, medical education.